EFEKTIVITAS MODEL SUGESTI IMAJINASI BERBANTUAN MEDIA BOARD GAME “TANYA” DALAM MENINGKATKAN KEMAMPUAN MENULIS PUISI - Pratama, Ananda; Hartati, Dian; Syafroni, Roni Nugraha (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This study aims to see the effectiveness of using the imagination suggestion model with the ‘Tanya’ board game media to improve the poetry writing ability of class VIII students at SMPN 1 Majalaya Karawang. This research was conducted using quantitative approach and quasi experimental method. Data were obtained through test and questionnaire techniques. The data obtained will go through normality test, independent sample t test, homogeneity, Mann Whitney test, and N-Gain test. The results showed that there was a significant capability difference between students who used the imagination suggestion model assisted by the board game media ‘Tanya’ and students who did not use the imagination suggestion model with the board game media ‘Tanya’. This is evidenced by the results of the N-Gain test of the posttest value in the experimental class of 56.1797 which is categorised as quite effective in improving the ability to write poetry.